The Services Provided to the Syrian Refugees in Azraq Camp During COVID-19 Pandemic by International Non-Governmental Organization - Aqel, Tasneem Amjad Deep; Akroush, Lubna Gudeh (Jordan Journal of Social Sciences, 2024)
This study aimed to identify the services provided International Non-Governmental Organization for Syrian Refugees in Azraq Camp during the COVID-19 Pandemic. A specific questionnaire was developed for this study to achieve the study objectives. Moreover, the study sample consisted of (398) Syrian refugees residing in four villages and who are over (25) years old. The study data were analyzed using appropriate statistical methods and the Statistical Package for the Social Sciences (SPSS) program. The most significant results include the presence of Syrian volunteers inside the community centers has contributed to delivering social services to the refugees inside the camp, taking into consideration confidentiality and privacy. The health centers inside the camp are easy to access in addition to reproductive health and nutrition departments. International Non-Governmental Organizations also contributed to providing short-term job opportunities and encouraged the refugees to adopt their own productive projects. Finally, International Non-Governmental Organizations also provide educational services for all students without exception taking into consideration the equipped places. The study concluded with the following Encouraging International Non-Governmental Organizations to recruit social workers to help the refugees identify their needs and solve their problems in coordination with the authorities. In addition, to focus on conducting the projects and programs that aim to enhance the refugees’ capabilities and contribute to creating and improving their incomes.